The Impact of Energy Innovations and Environmental Performance on the Sustainable Development of the EU Countries in a Globalized Digital Economy - Noja, Gratiela Georgiana; Cristea, Mirela; Panait, Mirela; Trif, Simona Mihaela; Ponea, Constantin Ștefan (Frontiers in Environmental Science, 2022)
The research conducted in this paper aims to examine the role of energy innovations, digital technological transformation, and environmental performance in enhancing the sustainable economic development of the European Union (EU) countries, widely shaped by the globalization process. An advanced empirical analysis is configured on a cross-sectional dataset of EU-27 Member States compiled at the level of 2018 based on several modern econometric procedures, namely robust regression, structural equation modelling (SEM) and network analysis through Gaussian graphical models (GGM). We apply the econometric procedures to firstly identify and assess the direct, indirect, and total interlinkages between all considered variables, as well as their further cumulated spillover impact on sustainable economic development. EU countries are afterward clustered according to the Ward method inset for hierarchical clustering by accounting for the level of financial and trade globalization (captured through the KOF Index of Globalization), environmental performance and sustainability (captured through the Environmental Performance Index - EPI), and the degree of integration of digital technologies (proxied through the Digital Economy and Society Index - DESI) for an in-depth assessment and tailored policy design. The main results highlight that there are significant beneficial effects induced by energy innovations, increased environmental performance and digital transformation on the sustainable development of EU countries, with notable differentiation among them. Policy guidelines and strategic directions are also enhanced and largely presented within the paper.